2016
DOI: 10.1002/cpt.416
|View full text |Cite
|
Sign up to set email alerts
|

Imaging transporters: Transforming diagnostic and therapeutic development

Abstract: Molecular imaging allows noninvasive assessment of drug distribution across pharmacological barriers. Thus, it plays an increasingly important role in efforts to understand the interactions of molecules with membrane transporters during drug development and in clinical pharmacology. We describe established and emerging imaging modalities utilized for studying transporter expression and function. We further present examples of how molecular imaging could provide insights into the contribution of transporters to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Among these, PET and SPECT are being applied in the clinic. However, both PET and SPECT involve health risk and are technically demanding (Mann et al, 2015, 2016). In this study we evaluated for the first time the feasibility of utilizing an alternative method, NIR, for assessing MDR1-mediated efflux transport in tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, PET and SPECT are being applied in the clinic. However, both PET and SPECT involve health risk and are technically demanding (Mann et al, 2015, 2016). In this study we evaluated for the first time the feasibility of utilizing an alternative method, NIR, for assessing MDR1-mediated efflux transport in tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Only in recent years, studies of MDR1 activity in solid tumors have become more feasible, with the introduction of non-invasive imaging techniques and the use of radiolabeled substrates such as 99m Tc-methoxyisobutylisonitrile ( 99m Tc-MIBI) and 11 C-verapamil (Piwnica-Worms et al, 1993; Chen et al, 1997; Gottesman et al, 2002; Del Vecchio et al, 2003; Eary et al, 2011). Nevertheless, PET and SPECT scans are associated with health risk since they involve ionizing radiation, are technically demanding and are costly (James and Gambhir, 2012; Mann et al, 2015, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted/untargeted metabolomics approaches or state-of-the-art imaging techniques, e.g. matrix-assisted laser desorption/ionisation (MALDI)-imaging, which allows label-free assessment of drugs or their metabolites or endogenous substrates within tissue samples, are likely to substantially boost the identification of transporter substrates, elucidating the importance of selected transporters for drug response [14]. A recent study by Yee et al demonstrated that the combination of results from genomic studies and metabolomic approaches enables the identification of novel endogenous transporter substrates with potential application as metabolite biomarkers or probes to determine clinically relevant DDIs [15].…”
Section: Integrative Technologies In Precision Medicinementioning
confidence: 99%